Antimony oxide-substituted sulfur-based solid electrolyte, composite positive electrode material, preparation method and application thereof
By replacing antimony with partial germanium in the sulfide solid electrolyte, the synthesis of antimony-based solid electrolyte replaced by antimony oxygen is solved, the problem of existing sulfide electrolytes being sensitive to air is achieved, better air stability and high ionic conductivity are achieved, and suitable for lithium-ion solid-state batteries.
Patent Information
- Application Number
- CN202411944307.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Existing sulfide solid electrolytes such as Li10GeP2S12 are sensitive to air/moisture, prone to toxic H2S, and the ionic conductivity decreases after air/moisture exposure, limiting its practical application.
By replacing antimony (Sb) with part of germanium (Ge) in the sulfide solid electrolyte, the antimony oxygen-substituted sulfur-based solid electrolyte is synthesized, and the weak acidity of Sb and oxygen (O) are used to replace the S position, the air stability and interface stability of the electrolyte are improved.
It improves the air stability of the sulfur-based solid electrolyte substituted by antimony oxygen, reduces the generation of toxic H2S in the air environment, and maintains high ionic conductivity, making it suitable for industrial use.
Smart Images

Figure CN119764535A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion solid-state batteries, and specifically relates to an antimony-oxygen-substituted sulfur-based solid electrolyte, a composite positive electrode material, and a preparation method and application thereof. Background Art
[0002] Solid-state batteries are batteries that use solid electrodes and solid electrolytes. They have high energy density and excellent safety, and are considered the "holy grail" of next-generation battery technology. Solid-state batteries fundamentally solve the safety risks and energy density bottlenecks of liquid batteries by using solid electrolytes instead of liquid electrolytes. Their high ionic conductivity and low resistance characteristics enable solid-state batteries to achieve higher energy density and faster charging speeds, making them particularly suitable for electric vehicles, energy storage systems and other fields.
[0003] Solid-state electrolytes (SSEs) are key materials for all-solid-state lithium batteries (ASSLBs) because their ionic conductivity, wide electrochemical window, stability, and other parameters dominate the performance and assembly of ASSBs. Compared with other types of SSEs, including oxide, polymer, halide, and borohydride materials, sulfide SSEs are particularly attractive due to their intrinsic high ionic conductivity (even exceeding 10 mS cm -1 ) and deformability. Among the various sulfide SSEs reported, Li 10 GeP2S 12 (LGPS) due to its 12mS cm -1 It has become one of the most promising candidates due to its ultrahigh ionic conductivity and successful application in ASSLB.
[0004] However, like most other sulfide SSEs, LGPS is very sensitive to air / moisture and produces toxic H2S when exposed to the ambient environment, which limits its practical application. In addition, the ionic conductivity of sulfide SSEs will decrease by several orders of magnitude after air / moisture exposure, making them unsuitable for industrial use.
[0005] Therefore, in order to improve the air stability of LGPS, it is urgent to develop an antimony oxide-substituted sulfur-based solid electrolyte and a composite positive electrode material based on the antimony oxide-substituted sulfur-based solid electrolyte for use in lithium-ion solid-state batteries. Summary of the invention
[0006] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing an antimony oxide-substituted sulfur-based solid electrolyte; the second purpose of the present invention is to provide an antimony oxide-substituted sulfur-based solid electrolyte prepared by the preparation method; the third purpose of the present invention is to provide a composite positive electrode material comprising the fluorinated solid electrolyte; the fourth purpose of the present invention is a method for preparing the composite positive electrode material; the fifth purpose of the present invention is to provide an application of a fluorinated solid electrolyte or a composite positive electrode material in the preparation of a lithium-ion solid-state battery.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing an antimony oxide-substituted sulfur-based solid electrolyte, the preparation method comprising the following steps:
[0009] Step 1: In an inert gas atmosphere, lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), antimony pentasulfide (Sb2S5), germanium disulfide (GeS2) and lithium oxide (Li2O) are mixed, and ball milling and grinding are performed in sequence to obtain a processed sample, and the sample is pressed into a sheet and placed in a quartz tube and sealed;
[0010] Step 2: high-temperature calcination is performed in an inert gas atmosphere, and quenching is performed after the calcination is completed to obtain an antimony-oxygen-substituted sulfur-based solid electrolyte.
[0011] The present invention proposes a method and application of replacing part of the germanium element (Ge) in LGPS with antimony (Sb), that is, synthesizing an antimony-oxygen-substituted sulfur-based solid electrolyte by a solid phase method, which, at an appropriate Sb content, will cause volume expansion, thereby opening the internal lithium ion channel and accelerating the Li + Migration. Meanwhile, Sb belongs to the same group as P, but is a much softer acid compared to P. The rigid covalent bond between Sb and S is low, and the rigid covalent bond between Sb and S has a low affinity for oxygen. In an air environment, the improved LGPS material has better air stability. Replacing the S position with O, oxygen (O) is used for sulfur (S) anion doping of LGPS-type SSE, which can improve the chemical and electrochemical stability of the material.
[0012] In the above preparation method, preferably, the purity of Li2S is ≥99.9%, the purity of P2S5 is ≥99%, the content of Sb in Sb2S5 is ≥60%, the purity of GeS2 is ≥99%, and the purity of Li2O is ≥99.9%.
[0013] In the above preparation method, preferably, in step 1, the molar ratio of lithium sulfide, phosphorus pentasulfide, antimony pentasulfide, germanium disulfide and lithium oxide is 10:(1-x):x:1:0.9y; wherein x is 0.01 to 0.15; and y is 1 to 11.
[0014] In the above preparation method, preferably, in step 1, the inert gas atmosphere is an argon glove box environment atmosphere, and the water content in the glove box is less than 1 ppm, and the oxygen content is less than 1 ppm.
[0015] In the above preparation method, preferably, the ball milling process is carried out in a ball mill jar, and the material of the ball mill jar is selected from zirconium oxide, polytetrafluoroethylene or hard polyvinyl chloride; the ball mill jar is corrosion-resistant and has a certain hardness.
[0016] In the above preparation method, preferably, the rotation speed of the ball mill is 200 to 600 rpm / min, and the ball milling time is 8 to 24 h.
[0017] In the above preparation method, preferably, in step 1, the grinding treatment adopts mechanical grinding, the rotation speed of the mechanical grinding is 200-600 rpm / min, and the grinding time is 2-6h.
[0018] In the above preparation method, preferably, the pressure at which the sample is pressed into a sheet is 300-500 MPa.
[0019] In the above preparation method, preferably, in step 2, the inert gas atmosphere is selected from a combination of one or more of argon, helium and nitrogen.
[0020] In the above preparation method, preferably, in step 2, the heating rate of the high temperature calcination is 5-10°C / min, the calcination temperature is 300-600°C, and the holding time is 12-24h.
[0021] In the above preparation method, preferably, the quenching is to quickly cool in 0°C ice water, and the quenching time is 10 to 30 minutes.
[0022] On the other hand, the present invention also provides an antimony oxide-substituted sulfur-based solid electrolyte, which is prepared by the above-mentioned preparation method.
[0023] On the other hand, the present invention also provides a composite positive electrode material, which comprises a positive electrode material and the antimony oxide-substituted sulfur-based solid electrolyte according to claim 6; wherein the mass ratio of the positive electrode material to the antimony oxide-substituted sulfur-based solid electrolyte is 60:40 to 80:20.
[0024] Among the above-mentioned composite positive electrode materials, preferably, the positive electrode material is selected from one or more combinations of LiCoO2, LiFePO4, and LiMn2O4, but is not limited thereto.
[0025] On the other hand, the present invention also provides a method for preparing the above composite positive electrode material, which comprises mixing the positive electrode material and the antimony oxide-substituted sulfur-based solid electrolyte, ball-milling the mixture, and pressing the mixture into sheets.
[0026] In the above preparation method, preferably, the rotation speed of the ball mill is 200-600 rpm / min, and the ball milling time is 2-6 h.
[0027] In the above preparation method, preferably, the pressure for pressing into tablets is 200-300 MPa, and the pressing time is 10-20 min.
[0028] In the above preparation method, preferably, the pressed tablets are small discs, and the diameter of the small discs is 10 to 12 mm.
[0029] On the other hand, the present invention also provides the use of the above-mentioned antimony oxide-substituted sulfur-based solid electrolyte or the above-mentioned composite positive electrode material in the preparation of lithium-ion solid-state batteries.
[0030] In the above application, preferably, the solid-state battery is formed by stacking and pressing a composite positive electrode material, an antimony oxide-substituted sulfur-based solid electrolyte and an indium foil in sequence, and optionally also includes a negative electrode shell, a spring, a gasket and a positive electrode shell.
[0031] In the above application, preferably, the thickness of the indium foil is 10-20 μm; the pressure for pressing the indium foil is 80-150 MPa, and the pressing time is 10-20 min.
[0032] In the above application, preferably, the thickness of the composite positive electrode material is 60 to 80 μm; the thickness of the antimony oxide-substituted sulfur-based solid electrolyte is 3 to 10 μm; the pressure at which the composite positive electrode material is pressed to the antimony oxide-substituted sulfur-based solid electrolyte is 300 to 500 MPa; and the pressing time is 10 to 20 min.
[0033] Beneficial effects of the present invention:
[0034] (1) The antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO) of the present invention adopts a solid phase synthesis method, which has a simple process flow, a low synthesis temperature, and is commercially feasible.
[0035] (2) The present invention utilizes Sb- and O-containing compounds to improve the sulfur-based solid electrolyte, making full use of the weak acidity of Sb and the substitution of O for S sites, effectively improving the air stability and interface stability of the electrolyte material without affecting the ionic conductivity; at the same time, when exposed to the surrounding environment, the generation of toxic H2S is reduced.
[0036] (3) The surface of the composite positive electrode material prepared by using LGS PSO in the present invention also contains an oxygen atom layer of the solid electrolyte, which is helpful for the subsequent network formation.
[0037] (4) The present invention adopts a composite positive electrode material + antimony oxide-substituted sulfur-based solid electrolyte + indium foil negative electrode, and adopts high-pressure stamping to form a sheet, thereby improving the interface characteristics; the entire structural system is solid, and the impedance of the assembled battery is relatively small.
[0038] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 Schematic diagram of the atomic structure of the antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and a schematic diagram of the assembled solid-state battery component structure.
[0041] Figure 2 This is a comparison chart of H2S release at different storage times of the antimony oxide substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1.
[0042] Figure 3 A comparison chart of rate performance curves and charge-discharge curves of battery assembly tests of the antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1.
[0043] Figure 4 This is a comparison chart of infrared and XRD spectra analysis of the antimony oxide substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0045] Embodiment 1:
[0046] This embodiment provides an antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO) and a preparation method thereof, the preparation method comprising the following steps:
[0047] (1) In a glove box, 4.6 g of Li2S (converted molar mass is 0.1 mol), 1.934 g of P2S5 (converted molar mass is 8.7 mmol), 0.525 g of Sb2S5 (converted molar mass is 1.3 mmol), 1.36 g of GeS2 (converted molar mass is 10 mmol) and 0.027 g of Li2O (converted molar mass is 0.9 mmol) were weighed into a zirconia mill.
[0048] (2) Setting the jar mill speed to 400 rpm / min and the jar mill time to 12 h, starting jar milling, and using mechanical grinding after mixing the sample to ensure the uniformity of the particles; setting the mechanical grinding speed to 400 rpm / min and the grinding time to 4 h, starting mechanical grinding, taking out the sample after grinding, and then pressing the sample into a tightly packed state under a 400 MPa press, and finally putting it into a quartz tube, which is sealed and taken out from the glove box.
[0049] (3) The sealed quartz tube is placed in a high-temperature furnace and argon gas is introduced. The sample is then heated to 500°C at a heating rate of 10°C / min and then the heating is stopped. The sample is calcined at 500°C for 12 hours and then cooled. The cooled sample is then taken out and quickly placed in an ice-water mixture at 0°C for quenching. The quenching time is maintained for 15 minutes. The sample is then taken out to obtain an antimony-oxygen-substituted sulfur-based solid electrolyte, which is recorded as: LGSPSO.
[0050] The structural diagram of this material is shown in Figure 1 As shown in (a), the Ge atoms at the Ge position are partially replaced by Sb atoms, and the S atoms at the S position are partially replaced by O atoms. The weak acidity of Sb makes it more stable in the air than Ge. O atoms are more stable than S, and when they come into contact with air, they release less H2S gas (the number of S atoms decreases).
[0051] This embodiment also provides a composite positive electrode material further prepared based on the prepared antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO), and the preparation method of the composite positive electrode material comprises the following steps:
[0052] (1) A total of 5 g of the positive electrode material LiCoO2 and the antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO) sample prepared in this example were weighed in a mass ratio of 70:30, and then mixed and ball-milled in a pot mill at 400 rpm / min for 4 h to obtain a composite positive electrode material.
[0053] This embodiment also provides a method for assembling a battery using the composite positive electrode material and the antimony oxide-substituted sulfur-based solid electrolyte. The specific method includes the following steps:
[0054] (1) 100 mg of the prepared LGSPSO was weighed and then pressed into a small disc with a diameter of 12 mm at a pressure of 250 MPa. The thickness of the LGSPSO was adjusted to 10 μm by pressure control.
[0055] (2) Weigh 15 mg of the composite cathode material sample prepared above and evenly spread it on the LGSPSO small disc pressed in step (1), then press the composite cathode material and electrolyte material again at a pressure of 360 MPa, adjust the thickness of the composite cathode material to 70 μm by pressure control, and take out the electrolyte and cathode material (such as ) at the double-layer interface after pressing after maintaining the pressure for 15 min. Figure 1 , as shown in (b) in the figure).
[0056] (3) A 15 μm thick indium foil was punched into a small disc with a diameter of 12 mm using a punching machine. The disc of indium foil was then placed on the side of the other side of the electrolyte as the negative electrode. The sample was then taken out after pressing at a pressure of 150 MPa for 10 min.
[0057] (10) The negative electrode shell, spring, gasket, the prepared target sample (the side close to the gasket is indium foil), and the positive electrode shell are assembled and sealed with a sealing machine. The battery is then placed in an oven at 35°C for activation for about 4 hours and then taken out.
[0058] Comparative Example 1:
[0059] As a comparison, this comparative example provides a sulfur-based solid electrolyte and a preparation method thereof, the preparation method comprising the following steps:
[0060] (1) In a glove box, weigh 4.6 g of Li2S (converted molar mass is 0.1 mol), 1.934 g of P2S5 (converted molar mass is 8.7 mmol), and 1.36 g of GeS2 (converted molar mass is 10 mmol) into a zirconia mill.
[0061] (2) Setting the jar mill speed to 400 rpm / min and the jar mill time to 12 h, starting jar milling, and using mechanical grinding after mixing the sample to ensure the uniformity of the particles; setting the mechanical grinding speed to 400 rpm / min and the grinding time to 4 h, starting mechanical grinding, taking out the sample after grinding, and then pressing the sample into a tightly packed state under a 400 MPa press, and finally putting it into a quartz tube, which is sealed and taken out from the glove box.
[0062] (3) The sealed quartz tube is placed in a high-temperature furnace and argon gas is introduced. The sample is then heated to 500°C at a heating rate of 10°C / min and then the heating is stopped. The sample is calcined at 500°C for 12 hours and then cooled. The cooled sample is then taken out and quickly placed in an ice-water mixture at 0°C for quenching. The quenching time is maintained for 15 minutes. The sample is then taken out to obtain a sulfur-based solid electrolyte, which is recorded as: LGPS.
[0063] As a comparison, this comparative example also provides a composite positive electrode material further prepared based on the prepared sulfur-based solid electrolyte (LGPS), and the preparation method of the composite positive electrode material comprises the following steps:
[0064] (1) A total of 5 g of the positive electrode material LiCoO2 and the sulfur-based solid electrolyte (LGPS) sample prepared in this example were weighed in a mass ratio of 70:30, and then mixed and ball-milled in a pot mill at 400 rpm / min for 4 h to obtain a composite positive electrode material.
[0065] The battery assembly of Comparative Example 1 uses the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1 and the composite positive electrode material prepared in Comparative Example 1. The specific assembly of the battery includes the following steps:
[0066] (1) 100 mg of the LGPS prepared above was weighed and then pressed into a small disc with a diameter of 12 mm at a pressure of 250 MPa.
[0067] (2) Weigh 15 mg of the composite positive electrode material sample prepared in the above comparative example 1 and spread it evenly on the LGPS small disc pressed in step (1). Then, press the composite positive electrode material and electrolyte material again at a pressure of 360 MPa. After maintaining the pressure for 15 minutes, take out the electrolyte and positive electrode material at the double-layer interface after pressing.
[0068] (3) A 15 μm thick indium foil was punched into a small disc with a diameter of 12 mm using a punching machine. The disc of indium foil was then placed on the side of the other side of the electrolyte as the negative electrode. The sample was then taken out after pressing at a pressure of 150 MPa for 10 min.
[0069] (10) The negative electrode shell, spring, gasket, the prepared target sample (the side close to the gasket is indium foil), and the positive electrode shell are assembled and sealed with a sealing machine. The battery is then placed in an oven at 35°C for activation for about 4 hours and then taken out.
[0070] Test experiment:
[0071] The buckle power prepared in Example 1 of the present invention and Comparative Example 1 was tested for buckle power performance, and the specific test process is as follows:
[0072] Let stand for 2h→rate charge 0.1C, voltage ≤4.2V→constant current and constant voltage charge 0.05mA→rate discharge 0.1C, voltage ≤2.0v→let stand for 10min→rate charge 0.1C, voltage ≤4.2V→constant current and constant voltage charge 0.05mA→rate discharge 0.1C, voltage ≤2.0v→let stand for 10min.
[0073] The experimental results are as follows Figure 2 to Figure 4 shown.
[0074] Figure 2 This is a comparison chart of H2S release at different storage times of the antimony oxide substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1.
[0075] Depend on Figure 2 It can be seen that: with the passage of time, the gas production is increasing. The gas production increases relatively quickly within 90 minutes, and the growth rate is relatively slow after 90 minutes. Compared with the LGPS material, the H2S release of the LGSPSO material has been significantly improved. At 480 minutes, its gas production is only half of that of the LGPS material.
[0076] Figure 3 A comparison chart of rate performance curves and charge-discharge curves of battery assembly tests of the antimony oxide-substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1.
[0077] Depend on Figure 3 It can be seen that (a) in the figure is a rate performance curve. As can be seen from the figure, as the rate increases, its capacity is constantly decreasing, but the rate performance of the LGSPSO material is better. At 0.2C, the capacity is about 25mA / g higher than that of LGPS. (b) in the figure is a charge and discharge curve at 0.1C. It can be seen from the figure that LGPS has a capacity of only 114mAh / g, while the LGSPSO material has a capacity of 132mAh / g, which is a significant improvement.
[0078] Figure 4This is a comparison chart of infrared and XRD spectra analysis of the antimony oxide substituted sulfur-based solid electrolyte (LGSPSO) prepared in Example 1 of the present invention and the sulfur-based solid electrolyte (LGPS) prepared in Comparative Example 1.
[0079] Depend on Figure 4 It can be seen that (a) in the figure is an infrared analysis diagram. It can be seen from the figure that at 1050cm -1 The LGSPSO material has a PO bond peak, while the LGPS material has no PO bond, only PS bonds, indicating that part of the S in the LGPS material is replaced by O. (b) in the figure is the XRD spectrum. It can be seen from the figure that the peaks in relative positions are shifted to the left, indicating that the unit cell volume has expanded, mainly because Sb replaces part of Ge.
[0080] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing an antimony oxide-substituted sulfur-based solid electrolyte, characterized in that: The preparation method comprises the following steps: Step 1: In an inert gas atmosphere, lithium sulfide, phosphorus pentasulfide, antimony pentasulfide, germanium disulfide and lithium oxide are mixed, and ball milling and grinding are performed in sequence to obtain a processed sample, and the sample is pressed into a sheet and placed in a quartz tube and sealed; Step 2: high-temperature calcination is performed in an inert gas atmosphere, and quenching is performed after the calcination is completed to obtain an antimony-oxygen-substituted sulfur-based solid electrolyte.
2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of lithium sulfide, phosphorus pentasulfide, antimony pentasulfide, germanium disulfide and lithium oxide is 10:(1-x):x:1:0.9y; wherein x is 0.01 to 0.15; and y is 1 to 11.
3. The preparation method according to claim 1, characterized in that: In step 1, the inert gas atmosphere is an argon glove box environment atmosphere, the water content in the glove box is less than 1 ppm, and the oxygen content is less than 1 ppm; Preferably, the ball milling process is carried out in a ball mill jar, and the material of the ball mill jar is selected from zirconium oxide, polytetrafluoroethylene or hard polyvinyl chloride; Preferably, the rotation speed of the ball mill is 200-600 rpm / min, and the ball milling time is 8-24 h.
4. The preparation method according to claim 1, characterized in that: In step 1, the grinding process adopts mechanical grinding, the rotation speed of the mechanical grinding is 200-600 rpm / min, and the grinding time is 2-6 hours; Preferably, the pressure at which the sample is pressed into a sheet is 300-500 MPa.
5. The preparation method according to claim 1, characterized in that: In step 2, the inert gas atmosphere is selected from a combination of one or more of argon, helium and nitrogen; Preferably, the heating rate of the high temperature calcination is 5 to 10°C / min, the calcination temperature is 300 to 600°C, and the holding time is 12 to 24h; Preferably, the quenching is performed by rapidly placing the product into 0° C. ice water for cooling, and the quenching time is 10 to 30 minutes.
6. An antimony oxide-substituted sulfur-based solid electrolyte prepared by the preparation method according to any one of claims 1 to 5.
7. A composite positive electrode material, characterized in that: The composite positive electrode material comprises a positive electrode material and the antimony oxide-substituted sulfur-based solid electrolyte according to claim 6; wherein the mass ratio of the positive electrode material to the antimony oxide-substituted sulfur-based solid electrolyte is 60:40 to 80:
20.
8. The composite positive electrode material according to claim 7, characterized in that: The positive electrode material is selected from one or more combinations of LiCoO2, LiFePO4, and LiMn2O4.
9. A method for preparing the composite positive electrode material according to claim 7 or 8, the method comprising mixing the positive electrode material and the antimony oxide-substituted sulfur-based solid electrolyte, ball milling and pressing into sheets; Preferably, the ball milling speed is 200-600 rpm / min, and the ball milling time is 2-6 h; Preferably, the pressure for pressing into tablets is 200-300 MPa, and the pressing time is 10-20 min; Preferably, the pressed tablets are small discs, and the diameter of the small discs is 10 to 12 mm.
10. Use of the antimony oxide-substituted sulfur-based solid electrolyte prepared by the preparation method according to any one of claims 1 to 5, or the antimony oxide-substituted sulfur-based solid electrolyte according to claim 8, or the composite positive electrode material according to claim 7 or 8, or the composite positive electrode material prepared by the preparation method according to claim 9 in the preparation of lithium-ion solid-state batteries; Preferably, the solid-state battery is formed by stacking and pressing a composite positive electrode material, an antimony oxide-substituted sulfur-based solid electrolyte, and an indium foil in sequence under high pressure, and may also include a negative electrode shell, a spring, a gasket, and a positive electrode shell; Preferably, the thickness of the indium foil is 10 to 20 μm; the pressure of pressing the indium foil is 80 to 150 MPa, and the pressing time is 10 to 20 min; Preferably, the thickness of the composite positive electrode material is 60 to 80 μm; the thickness of the antimony oxide-substituted sulfur-based solid electrolyte is 3 to 10 μm; the pressure at which the composite positive electrode material is pressed to form the antimony oxide-substituted sulfur-based solid electrolyte is 300 to 500 MPa; and the pressing time is 10 to 20 min.